The ghost - Steel, Danielle (London : Corgi Books, 1998)
With a wife he loves and an exciting London-based career, architect Charles Waterston's life seems in perfect balance. Nothing in his comfortable existence prepares him for the sudden end to his ten-year marriage$1 (Bor his unwanted transfer to his firm's New York office. With nothing left to lose, Charlie takes a leave of absence from his job to drive through New England, hoping to make peace with himself.s
Keywords: Spirits -- Fiction; Love stories